Necrotizing cellulitis of the cervix mediastin - Taruselli, Roberto; Moure, Luis; Delbene, Roberto; Maestro, Marta; Morelli, Raúl (Cirugía del Uruguay, 2003)
Case history consisted of 2 patients suffering from dental origin Cervico-Mediastinal Necrotizing Cellulitis. As a first step the authors proceeded to analyze two dissemination paths, the more frequent etiologies and clinical presentation. Cervico-thoracic CT scanning was deemed to be the best line of detection far mediastinal involement exploration. This was followed by a debate as to which should be the surgical approach, whether cervical o cervicothoracic, the conclusion being that the best procedure would be the videothrorascopic approach in experienced hands.